10.1016/s1544-8800(12)70204-x (CrossRef Listing of Deleted DOIs, 2000)
Background Eating a whole-food, plant-predominant diet reduces chronic systemic inflammation, which can improve pain in people with chronic musculoskeletal conditions. However, 85% of people have dietary perceptions that do not accurately reflect their actual dietary quality. Objective To determine whether patients' dietary perceptions align with dietary quality, assess correlations between dietary perception and lifestyle metrics, and evaluate how dietary perceptions relate to outcomes following Lifestyle Medicine (LSM) program completion. Design Retrospective review of repository data. Setting Tertiary orthopedic center. Patients Seven hundred eighty-three adults enrolled in the LSM program from March 2022-August 2024. Interventions Patients chose to participate in an intensive (multiple-visit) or selective (single-visit) track of the LSM program to treat musculoskeletal conditions and chronic diseases. Main outcome measures Dietary perceptions were evaluated by asking patients if they had a healthy diet. Dietary quality was assessed by determining percentages of whole-food on a plate per meal (healthy diet: ≥50%). Lifestyle metrics included physical activity, sleep health, anxiety/depression, social connections, and smoking status. Program outcomes included the ability to attain goals to have hip or knee arthroplasty in a subset of 158 patients. Results Of the 783 patients (74.3% female, 60.3 ± 10.8 years), 60.4% (95% confidence interval [CI]: 56.9%-63.9%) had healthy dietary perceptions. Lifestyle metrics did not differ between patients with concordant versus discordant dietary perceptions (p > .05). Compared to patients with unhealthy dietary perceptions, patients with healthy dietary perceptions were more likely to be physically active (41.5% vs. 33.5% [p = .025]) and report good social connections (94.6% vs. 82.3% [p < .001]), with less sleep impairment (73.9% vs. 86.1% [p < .001]) and anxiety/depression (42.9% vs. 59.5% [p < .001]). Hip or knee arthroplasty rates did not differ by dietary perception status. Conclusion Perceiving one's diet as healthy, rather than concordance with actual dietary quality, was associated with favorable lifestyle metrics. This suggests positive health perceptions may help predict engagement in other healthy behaviors.